Performance analysis of Arithmetic Mean method for solving composite 6-point closed NewtonâCotes quadrature algebraic equation - Muthuvalu, M.S. (World Scientific Publishing Co. Pte Ltd, 2018)
The main focus of the paper is to study the performance of Arithmetic Mean (AM) iterative method in solving large and nonsingular dense linear system arising from the composite 6-point closed NewtonâCotes quadrature (6-CCNC) approximation of inhomogeneous linear Fredholm integral equations of the second kind. The derivation and implementation of the method are discussed. Some numerical results are also presented. Â© 2019 World Scientific Publishing Company